The Effect Of Final Irrigation Materials And Techniques On The Cleanliness Of The Smear Layer In The Apical Third Of The Root Canal - Maranantan, Helga Anindyastika; Ratih, Diatri Nari; Mulyawati, Ema (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
17% EDTA is a chelating agent used to clean the smear layer. Novel silver citrate (NSC) is a new material with the same use, while 0.2% chitosan nanoparticles are a material that has been widely studied. The agitation technique influences smear layer cleanliness by optimizing the penetration of irrigation material. Agitation techniques are sonic and ultrasonic agitation techniques; each has its advantages and disadvantages. The research objective is to evaluate the effect of final irrigation materials, agitation techniques, and a combination of both on the cleanliness of the smear layer in the apical third of the root canal.Forty-five premolars were prepared with a rotary instrument. Samples then randomly divided into 3 experimental groups (n=15). Group 1 used 17% EDTA, group 2 used NSC, and group 3 used 0.2% nanoparticle chitosan. Each group was divided into three subgroups (n=5) with subgroup A using manual agitation technique, subgroup B sonic agitation, and subgroup C ultrasonic agitation. The samples were sectioned and then examined under SEM with 5000x magnification to evaluate the cleanliness of the smear layer. The results from SEM were scored and then analyzed using Chi-Square test (IBM SPSS Statistics 29.0.1.0).Final irrigation agents of 17% EDTA, NSC, and 0.2% chitosan nanoparticles resulted in the same cleanliness of the smear layer (p˃0.05). The ultrasonic agitation technique showed better cleanliness of the smear layer than the sonic agitation and manual agitation techniques (p˂0.05). The final irrigation material combined with agitation techniques resulted in the same cleanliness of the smear layer (p˃0.05).